Influência do tipo de pôntico, número de pilares e tipo de aplicação de carga na distribuição das tensões em prótese fixa em cantilever análise por elementos finitos - Branco, Carolina Assaf (2008)
Cantilever fixed prosthodontics are satisfactory rehabilitation alternatives when osseointegrated implants are not indicated, which justifies the important knownledgment with respect to a correct indication and technical procedures. The aim of this study was to evaluate the stress distribution on support dental structures and prosthesis framework by finite elements method. The pontic anatomy (premolar or molar), type and number of abutments (one or two, single or bilateral, anteriorly or posteriorly faced) e occlusal load (premature contact or normal occlusion). A real model composed by a canine, first and second premolars, first, second and third molars was employed for the creation of the 2D mathematical models, simulating all the involved dental and prosthetic structures and studying stress distribution by finite elements method under normal occlusal load or premature contact near or distant from the primary prosthesis conector. Five percent of physiologic masticatory load was used in the simulation. The plotted images were qualitatively analyzed. In the quantitative analysis stress values were collected at two selected lines in the models, line A, created 2mm above cortical bone at the edentulous space, and line B, which was located at the center of prosthesis conectors. The regions with the most pronouncing stress concentrations were the cortical bone, roots of abutment teeth and prosthesis conectors. Stress were lower and better distributed on conventional fixed prosthesis, irrespective of the type of pontic. The models, for both premolar or molar pontics, under premature contact load condition showed the most unfavorable stress conditions, principally when it occurred distant from the primary conector. Within the limitations of this study it is possible to conclude that conventional fixed prosthesis show stress distribution in a more favorable condition than cantilever prosthesis. The most extensive pontic (molar) results in more unfavorable and greater stress at adjacent structures. The inclusion of a second abutment is more favorable to support dental structures and prosthesis framework when premature contact load condition takes place.